Sosialisasi anti bullying sebagai upaya pencegahan perundungan di sekolah dasar - Lailatul Muarofah Hanim; Masqotul Imam Romadlani; Muhammad Bima; Saulia Akhtari; Bisma Satriya Adzanandho; Isza Darika (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
This study investigates how students from Trunojoyo Madura University (UTM) conducted anti-bullying socialization in the Thematic Real Work Lecture (KKN-T) program on August 9, 2025, at SDN 3 Jaddih, Socah District, Bangkalan Regency. The purpose of this activity was to respond to the numerous cases of bullying in elementary schools and social media. The focus of this activity was to raise awareness among fifth-grade students about the dangers of bullying on social relationships and mental health from an early age. Conceptual socialization, experience sharing, educational games such as role-playing, and the introduction of the slogan “Bullying NO, Good Friends YES” were some of the methods used. Fifty fifth-grade students, along with teachers and the principal, were the main participants. Data was collected through direct observation of the activities, casual conversations with participants, and recording various findings in the field. The results showed that the students were very enthusiastic; some of them shared their experiences of bullying or being victims, such as being beaten or ridiculed. The educational games successfully improved the students' understanding, while the appreciation given by the school showed that this was in line with the school's efforts to create a friendly learning environment. The results of the discussion were linked to active learning theory and emphasized the possibility of reducing incidents of abuse. This activity demonstrates that anti bullying outreach can be effective preventive strategy for raising elementary school students awareness of the dangers of bullying. Therefore, it is recommended that similiar programs be implemented on an ongoing basis, involving teachers and parents. So, that bullying preventation efforts can be carried out more effectively.